"Fotovvat - Nameh," The letter of Generosity - Ali Akbar Khan - Mohammadi (صفه)
The book of chiverly, or as stated before, "the letter of Generosity" is a number of practical and obsessional codes which all professions have not only relied upon, but have also set their relations with each other and—other members of the society as well.Of such letters, is the "Generosity letter of the builders", which considers all architects, builders and every other person working in this field. This letter, which has been kept at a Turkish library, is rather incomplete and lacks the neccessary datails. However, it remains to be the only known text of its kind.The present letter is in two parts. First, it reflects, in general, the principles and appointed guidelines and second, the same principles have been presented in the from of questions and answers in order to reveal all the necessary details.The first part consists of twelve sections which generally emphasis on such virtues as abundance, security, modesty, sincerity and loyalty among the members of the profession. However, the second section includes the neccessary directions and guidlines and also narrates, the statements made by the Prophet, the twelve Imams of the the shi'ite faith and every distinguished expert who has worked in this field before.